The Influence of Psychological Empowerment & Turnover Intention Through Career Growth in Pharmaceutical Companies, Lahore, Pakistan - Sameera Amjad; Hafiz Muhammad Basit; Ahmed Usman Khan; Hamza Akram (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2022)
The aim of this study is to examine the impact of psychological empowerment on employee turnover intention with the moderating effect of career growth. A cross sectional survey was used to collect data. A total of 207employees of different pharmaceutical companies in Lahore, were participating through random sampling in this survey. Our finding shows that the two dimensions of psychological empowerment (emotional and relational) have an inverse relationship with intention to quit, whereas (behavioral and cognitive) psychological empowerment is not significantly related to the theory. Career growth shows moderating effect on relational psychological empowerment and turnover intention, although there is no moderating impact found in the remaining dimension of psychological empowerment (cognitive, emotional and behavioral) and turnover intention. Because of the strategic importance of human capital in an organization, it is important for the continuity of the pharmaceutical firms to retain their employees by providing best career growth path to move the employees as well as organization to the next level and save the human capital cost